Effects of a high-intensity psychosocial intervention among child–parent units in pediatric oncology. Issue 5 (October 2020) - Zucchetti, Giulia; Ambrogio, Giorgia; Bertolotti, Marina; Besenzon, Luigi; Borghino, Fabio; Candela, Filippo; Galletto, Chiara; Fagioli, Franca
Aim: To compare the efficacy of a high-intensity psychosocial intervention with standardized usual care in countering psychosocial complexity among child–parent units in a pediatric oncology setting. Methods: Two hundred pediatric oncology patients and their parents were recruited from Italian hospitals. A total of 81 child–parent units were assigned to the high-intensity psychosocial intervention and 119 child–parent units to standardized usual care. Psychosocial factors were assessed before and 1 year after intervention to measure efficacy. Results: More improvements over time were observed in the high-intensity intervention group of child–parent units compared to the standard intervention group. Conclusion: An intensive, structured, and tailored high-intensity intervention positively affects the psychosocial factors of child–parent units. Patients and families should have access to intensive psychosocial support throughout the cancer trajectory.